Torontos: representations of Toronto in contemporary Canadian literature - Smith, William Leon (2012)
This thesis examines how representations of Toronto in contemporary Canadian literature engage with place and further an understanding of spatial innovation in literature. Acknowledging the Canadian critical tradition of discussing place and space, the thesis moves the focus away from conventional engagements with wilderness motifs and small town narratives. In this way the thesis can be seen to respond to the nascent critical movement that urges engagement with contemporary urban spaces in Canadian literature. Responding to the critical neglect of urban representation, and more particularly, representations of Toronto in Canadian literary criticism, this thesis examines Toronto as a complex and contradictory site of symbolic power across critical, political and popular discourses. Furthermore, this thesis repositions an understanding of Toronto by paying attention to literary texts which depict the city's negotiation of national, local and global forces. The thesis seeks to understand the multiplicity of the city in lived, perceived and conceived forms - seeing Toronto as Torontos.